Recent insights into the management of treatment-resistant pediatric atopic dermatitis. Issue 2 (25th May 2022) - Naik, Piyu Parth
Abstract : Atopic dermatitis (AD) is a prevalent protracted inflammatory skin condition that affects approximately 12% of children globally. Topical remedies, such as pharmacologic and nonpharmacologic management, and off-label systemic medicines, have traditionally been used to treat pediatric AD patients. To minimize comorbidities, sleep disturbances, pruritus, and signs of inflammation and improve the patient's quality of life, it is vital to optimize severe AD management in pediatric patients. Treatment resistance can be caused by a variety of circumstances, including deficient obedience or inappropriate medicine usage, a shortage of adequate pharmaceuticals, hypersensitivity reciprocation to local application of therapeutics, cutaneous infections, and other infuriating ecological provoking factors. If these elements are eliminated, a skin biopsy is required to exclude other AD-like cutaneous disorders. New regimens that target peculiar avenues with improved proficiency and promise minimal adverse events have resulted from recent developments and understanding of the etiology of AD. Although the condition of most patients improves quickly with this treatment, some do not respond well. In this review, the author discusses the management of treatment-resistant atopic dermatitis, with an emphasis on the pediatric population.